2007
DOI: 10.1111/j.1365-2133.2007.08249.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that dysregulated DNA mismatch repair characterizes human nonmelanoma skin cancer

Abstract: In combination with previously established roles for MMR proteins in response to UVB-induced DNA damage, our data point towards an expanded perspective of the importance of MMR proteins in the suppression of UVB-induced tumorigenesis and, potentially, tumour behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 52 publications
2
31
0
1
Order By: Relevance
“…These findings suggest that defective MMR is unlikely to play a significant role in the development of SCC in OTRs on azathioprine. MMR protein expression was also retained in SCCs from immunocompetent individuals, consistent with other studies that have shown that sporadic SCCs do not typically show loss of MMR expression 29,35 and rarely exhibit MSI. 36 By way of comparison, around 20% of sporadic colorectal carcinomas are MSI positive.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings suggest that defective MMR is unlikely to play a significant role in the development of SCC in OTRs on azathioprine. MMR protein expression was also retained in SCCs from immunocompetent individuals, consistent with other studies that have shown that sporadic SCCs do not typically show loss of MMR expression 29,35 and rarely exhibit MSI. 36 By way of comparison, around 20% of sporadic colorectal carcinomas are MSI positive.…”
Section: Discussionsupporting
confidence: 90%
“…29,33 Mathiak et al 33 examined MLH1 and MSH2 protein levels in 28 skin tumours (20 sebaceous gland tumours, four sebaceous hyperplasias, three keratoacanthomas and one SCC) and showed that MSH2 and MLH1 protein expression correlated with the results of molecular genetic analysis in over 90% of cases. Twenty tumours came from 10 patients with HNPCC ⁄MTS with known germline mutations in an MMR Scoring key: 0, < 10% cells; 1, 11-50% cells; 2, 51-80% cells; 3, 81-100% cells.…”
Section: Discussionmentioning
confidence: 97%
“…Quinn et al detected MSI in a percentage lower than 5% [27] whereas a recent study reported that BCCs of azathioprine-treated organ transplant recipients were microsatellite stable even in the highly MSI-sensitive BAT25 and BAT26 markers [28]. Moreover Young et al reported no MSI in 32 Squamous Cell Carcinomas (SCCs) after analyzing the sensitive BAT26 marker [29]. They also reported increased levels of MMR proteins (MSH2, MSH3, MSH6, MLH1 and PMS2) mainly in SCCs and at a lesser extent in BCCs compared with normal skin and no association between the presence of MSI and loss of expression of any examined MMR protein.…”
Section: Discussionmentioning
confidence: 92%
“…They also reported increased levels of MMR proteins (MSH2, MSH3, MSH6, MLH1 and PMS2) mainly in SCCs and at a lesser extent in BCCs compared with normal skin and no association between the presence of MSI and loss of expression of any examined MMR protein. Interestingly, they further describe a dysregulation of the MMR system [29]. The possible role of this dysregulation in the multistep process of carcinogenesis has to be elucidated.…”
Section: Discussionmentioning
confidence: 98%
“…MMR proteins are highly and ubiquitously expressed, 11 and evidence suggests that the correct ratio between these proteins is key to their function. [12][13][14][15][16][17][18] The MMR protein heterodimer MSH2·MSH6 (also known as MutS␣) detects both single base mismatches and small insertion-deletion loops (one or two nucleotides), whereas the MSH2·MSH3 heterodimer (also known as MutS␤) detects only insertion-deletion loops (two to 14 nucleotides). 10 Normally, MSH2·MSH6 is 10-fold more abundant than MSH2·MSH3.…”
mentioning
confidence: 99%